Single-Cell RNA Sequencing Reveals Smooth Muscle Cells Heterogeneity in Experimental Aortic Dissection - Xu, Cheng; Liu, Xiaowei; Fang, Xiaoxin; Yu, Lei; Lau, Hui Chong; Li, Danlei; Liu, Xiaoman; Li, Haili; Ren, Justin; Xu, Baohui; Jiang, Jianjun; Tang, Lijiang; et al. (Frontiers in Genetics, 2022)
Purpose: This study aims to illustrate the cellular landscape in the aorta of experimental aortic dissection (AD) and elaborate on the smooth muscle cells (SMCs) heterogeneity and functions among various cell types. Methods: Male Apolipoprotein deficient (ApoE−/−) mice at 28 weeks of age were infused with Ang II (2,500 ng/kg/min) to induce AD. Aortas from euthanized mice were harvested after 7 days for 10×Genomics single-cell RNA sequencing (scRNA-seq), followed by the identification of cell types and differentially expressed genes (DEGs). Gene Ontology (GO) enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis was conducted. Results: AD was successfully induced in ApoE−/− mice. scRNA-seq identified 15 cell clusters and nine cell types, including non-immune cells (endothelials, fibroblasts, and SMCs) and immune cells (B cells, natural killer T cell, macrophages, dendritic cells, neutrophils, and mast cells). The relative numbers of SMCs were remarkably changed, and seven core DEGs (ACTA2,IL6,CTGF,BGN,ITGA8,THBS1, and CDH5) were identified in SMCs. Moreover, we found SMCs can differentiate into 8 different subtypes through single-cell trajectory analysis. Conclusion: scRNA-seq technology can successfully identify unique cell composition in experimental AD. To our knowledge, this is the first study that provided the complete cellular landscape in AD tissues from mice, seven core DEGs and eight subtypes of SMCs were identified, and the SMCs have evolution from matrix type to inflammatory type.